1991
DOI: 10.1002/actp.1991.010420809
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stimulated depolarization currents in poly(acrylamide) films

Abstract: The charge storage mechanism in poly(aery1amide) films was studied by means of the technique of thermally stimulated depolarization currents (TSDC). The TSDC were measured as a function of field strength, temperature and time of polarization in dependence on the heating rate. One peak was observed on the TSDC spectra a t low polarizing temperatures, while two peaks occurred for higher polarizing temperatures. The first peak was attributed to dipole orientation and the second one to space charge polarization. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…It is well-known that restricted rotation about the carbon-to-nitrogen bond in a number of amides leads to the existence of geometrical isomers (Lewin et al 1975). The present case is similar those of salicylaldehyde (N-benzoyl) glycyl hydrazone (Rao and Singh 1991) and furfural (N-benzoyl)glycyl hydrazone (Lonibala 1992) where two isomers were shown in each case. These isomers are usually non-separable due to the relatively low barrier to rotation (Stewart and Sidall 1970).…”
Section: Nmr Spectrasupporting
confidence: 77%
“…It is well-known that restricted rotation about the carbon-to-nitrogen bond in a number of amides leads to the existence of geometrical isomers (Lewin et al 1975). The present case is similar those of salicylaldehyde (N-benzoyl) glycyl hydrazone (Rao and Singh 1991) and furfural (N-benzoyl)glycyl hydrazone (Lonibala 1992) where two isomers were shown in each case. These isomers are usually non-separable due to the relatively low barrier to rotation (Stewart and Sidall 1970).…”
Section: Nmr Spectrasupporting
confidence: 77%
“…It can be seen that the initial conductivity increases up to 87 • C, followed by a moderate increase up to 300 • C, and then a final rapid decrease from 300 to 441 • C. This behaviour was assigned to the conversion of polymer to metallic MgSi, elimination of organic components from the polymer phase to form the composites of magnesium silicate. Narasimha Rao and Subba [57] reported thermally stimulated discharge currents in the composite polymer as a function of the polarizing field strength and concluded that the Poole-Frenkel model describes the dominant mechanism. Blythe [58] stated that polyamides show pronounced ionic conduction effects at elevated temperatures, evidently as a result of the dissociation of amide groups to give protons [59].…”
Section: Conductivity Propertiesmentioning
confidence: 99%